The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1029/2009gl039427
|View full text |Cite
|
Sign up to set email alerts
|

Discrete classification and electron energy spectra of Titan's varied magnetospheric environment

Abstract: We analyse combined electron spectra across the dynamic range of both Cassini electron sensors in order to characterise the background plasma environment near Titan for 54 Cassini‐Titan encounters as of May 2009. We characterise the encounters into four broad types: Plasma sheet, Lobe‐like, Magnetosheath and Bimodal. Despite many encounters occurring close to the magnetopause only two encounters to date were predominantly in the magnetosheath (T32 and T42). Bimodal encounters contain two distinct electron popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
209
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(219 citation statements)
references
References 26 publications
3
209
0
Order By: Relevance
“…If the orbit of Titan marks the approximate magnetopause Rymer et al, 2009], then mapping Titan's orbit to the ionosphere very crudely suggests that the aurora itself does mark the open/closed boundary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the orbit of Titan marks the approximate magnetopause Rymer et al, 2009], then mapping Titan's orbit to the ionosphere very crudely suggests that the aurora itself does mark the open/closed boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Pitch angle distributions of lower-energy electrons (E < 26 keV) have been surveyed using data from the Cassini Plasma Spectrometer (CAPS) [Young et al, 2004]. These electrons exhibited butterfly, pancake, and field-aligned distributions that were interpreted in terms of inward and outward plasma motion driven by the centrifugal interchange instability in combination with azimuthal gradient and curvature drift [Rymer et al, 2009]. A preliminary report on the pitch angle distributions of energetic electrons indicated that magnetospheric electron (bidirectional) beams connect to the expected locations of Saturn's aurora [Saur et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…The electron impact rates used in this study are based on the CAPS electron fluxes measured during the TA encounter. The electron spectrum during this encounter is classified by Rymer et al (2009) as a plasma sheet encounter. The peak electron energies in this region run between 120-600 eV with the fluxes at the peak energy between 3.5 × 10 5 and 1.2 × 10 6 cm −2 s −1 sr −1 Rymer et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…The electron spectrum during this encounter is classified by Rymer et al (2009) as a plasma sheet encounter. The peak electron energies in this region run between 120-600 eV with the fluxes at the peak energy between 3.5 × 10 5 and 1.2 × 10 6 cm −2 s −1 sr −1 Rymer et al (2009). Using electron production rates based on the higher end of these ranges would increase the nightside ionospheric densities and hence the ion loss from that region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation